CONTRIBUTION TO RISK ANALYSIS OF AUTOMATIC TRAIN CONTROL MODULE (Perner's Contacts, 2009)
The contribution deals with methods of risk assessment according to the standard ČSN EN 61508. The risk category is assessed with use of ALARP principle and subsequently the safety integrity level SIL is determined using a risk diagram. The contribution presents an example of these procedures utilization for automatic train control module.
Keywords: SIL; ALARP; safety integrity level; automatic train control